Wewenang Pemerintah Daerah dalam Menjamin Keselamatan dan Keamanan Penerbangan Serta Pengembangan Bandar Udara - Grahadi Purna Putra; Bambang Daud (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research analyzes the authority of local governments in ensuring aviation safety and security through the regulation of the Airport Operation Safety Zone (Kawasan Keselamatan Operasi Penerbangan/KKOP) and spatial control around airports in Indonesia. The study employs a normative juridical method by examining statutory regulations, international standards from the International Civil Aviation Organization (ICAO), as well as relevant cases in Ahmad Yani Airport Semarang, Mutiara Sis Al Jufri Airport Palu, and Supadio Airport Pontianak. The results show that the authority of local governments is strategic but not absolute; it must be harmonized with national policies and international standards. In practice, the implementation is hampered by normative and practical challenges. Normative barriers include fragmented regulations, weak regional legal instruments, and the lack of incorporation of ICAO standards into local regulations. Implementation barriers involve limited technical capacity, insufficient resources, weak supervision, and socio-economic resistance related to land use around airports. These conditions result in ineffective spatial control, which directly affects aviation safety and airport development. The study suggests strengthening local regulations through specific bylaws on KKOP that align with national and international standards, improving the technical capacity of local apparatus, integrating obstacle registry systems, and establishing compensation or relocation mechanisms for affected communities. Cross-sectoral coordination between central government, local government, airport authorities, and stakeholders is also essential to ensure consistent policy implementation. This research contributes to the development of aviation law, regional autonomy, and the improvement of public safety in Indonesia.